TRUST AS A FACTOR OF A COMPETITIVE ADVANTAGE IN A HOTEL BUSINESS - Batorski, Jarema; Lentner, Agnieszka (Acta Scientiarum Polonorum. Oeconomia, 2010)
Trust is a factor of organizational learning. It is also a very important source of a competitive advantage of a tourist business. Openness is a major component of Trust Management. For instance, openness means that there is a necessity of getting information to employees about significant decisions taking place in their company. It should also encourage workers to interchange informations. Trust Management has a reference in a free information process which allows to enroll employees into business affairs. Openness also refers to the proceeding in case of confl icts. A manager should convince one’s subordinates, that one should not suppress disputes, but to aspire for untying them. In the paper, possibilities of using the model of Partnership Trust Tool in the hotel were presented. It was used originally for the measurement of trusting at American medical institutions.